PENGARUH LEVERAGE, GROWTH OPPORTUNITIES, DAN LIQUIDITY TERHADAP PENGAMBILAN KEPUTUSAN HEDGING PT. INDOSAT TBK - Widyagoca, IGusti Agung; Lestari, Putu Vivi (E-Jurnal Manajemen, 2016)
Corporate transactions with international companies is not only made in cash, payable or receivable arising as a result in the form of foreign currency, which makes the company suffered losses as well as profits. This study aims to determine the significance of the effect of partially Leverage, Growth Opportunities, current ratio, and the ratio Cash Against Use of Derivative Instruments Foreign Exchange Hedging Decision as PT. Indosat Tbk period of 2004 - 2014. By using associative method and technique of multiple regression analysis assisted with SPSS program, which includes the classic assumption test and partial test (t test) with a significance level (?) = 5 percent. Based on the results of data processing, obtained that leverage a significant negative effect on the decision Hedging, Growth opportunities and Cash ratio, but no significant negative impact on the decision Hedging while the current ratio is positive but not significant effect.
Keywords: hedging, derivative instruments, investment decisions